2017
DOI: 10.1037/a0040216
|View full text |Cite
|
Sign up to set email alerts
|

El ojo en la meta: Latino male undergraduates’ coping processes.

Abstract: As Latino males are entering and graduating from higher education at significantly lower rates than their counterparts, this study focused on their educational coping processes. Interviews with five upper-division Latino male undergraduates at a large predominantly White 4-year university revealed a range of coping processes which were self-protective and that helped them persist to graduation. In particular, spirituality was explored as a central cultural coping mechanism, and results indicated that Latinos h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 31 publications
(106 reference statements)
5
39
0
Order By: Relevance
“…Compared to extant research, self-identified Latinas typically outnumber their male peers in higher education (Castellanos et al, 2018; as well as in completing study surveys. Although no gender differences emerged, educational experiences and self-beliefs (e.g., confidence in one's ability to successfully complete academic tasks; Lopez, 2014) clearly differ by self-identified gender and subsequent cultural expectations (Gloria et al, 2017). How self-identified gender-related concerns inform students' sense of belonging or mattering within the university setting warrants study-for example, as Latino male undergraduates report using "angry face" or "walking angry" to cope proactively with others in the university context (i.e., defensive strategy to keep others away; Gloria et al, 2017), exploring how this self-preserving process may limit the contexts in which they engage (e.g., classroom, residence hall, campus) and in turn whether they feel like they belong and matter differently than their Latina peers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to extant research, self-identified Latinas typically outnumber their male peers in higher education (Castellanos et al, 2018; as well as in completing study surveys. Although no gender differences emerged, educational experiences and self-beliefs (e.g., confidence in one's ability to successfully complete academic tasks; Lopez, 2014) clearly differ by self-identified gender and subsequent cultural expectations (Gloria et al, 2017). How self-identified gender-related concerns inform students' sense of belonging or mattering within the university setting warrants study-for example, as Latino male undergraduates report using "angry face" or "walking angry" to cope proactively with others in the university context (i.e., defensive strategy to keep others away; Gloria et al, 2017), exploring how this self-preserving process may limit the contexts in which they engage (e.g., classroom, residence hall, campus) and in turn whether they feel like they belong and matter differently than their Latina peers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Using the self-determination theory, the concept addresses whether a person holds an activity with interest or importance in the environment such that intrinsic (internal) and extrinsic (external) motivation are evident (Deci & Ryan, 2002;Niemiec & Ryan, 2009). Specific to Latinx students, their motivation to attend college is often informed by their experience of the campus climate (Hurtado & Carter, 1997;Reynolds et al, 2010), cultural values (Phinney et al, 2006), and commitment to advance their family and community (Gloria et al, 2017). For example, reported that "mothers built high levels of aspirational capital by establishing high expectations of educational success and serving as strong sources of motivation" (p. 11) for 130 Latino male undergraduates.…”
Section: Psychological Dimension (Motivation)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jackson and Suizzo (2015) conducted focus groups and interviews with college-age Latinas in sciencerelated majors and found that their resilience and determination in regard to their science identity development was positively influenced by home environment, teacher influences, and school experiences. In turn, Gloria et al (2017) interviewed upper-division Latino male undergraduates and found that the students used a range of self-protective coping mechanisms, such as spirituality, that helped them persist to graduation. We strove to increase knowledge about the college experience of diverse students who attended a public university.…”
mentioning
confidence: 99%